Development of Student Performance Assessment Applications using Website-based Gamification Concept - Raudhatusholihat Amalia; Rahma Wahdiniwaty (Universitas Komputer Indonesia, 2023)
Violations that continue to increase, as if unconsciously, can affect the teacher's assessment of students. To overcome this issue, an application for student performance assessment was developed using the concept of web-based gamification to reduce the frequency of violations. The purpose of this study is to improve the quality of students by encouraging them to adhere to school rules and rewarding those who comply. The research employs the concept of gamification and a daily assessment method, whereby assessments are carried out every day and calculated monthly. This method involves communication, planning, modeling, and construction, culminating in deployment. The results show that the web-based assessment application, utilizing gamification methods, can effectively improve student behavior in a more positive direction. Additionally, testing of the black box functionality revealed successful results, demonstrating that the application is reliable and feasible for use. Overall, the application motivates students to improve their discipline in order to achieve good results